2015
DOI: 10.1007/s12094-015-1369-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors affecting survival in metastatic soft tissue sarcoma: an analysis of 110 patients

Abstract: Serum albumin, tumor size, hemoglobin and treatment modality affect survival in metastatic STS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
5
42
1
Order By: Relevance
“…Iqubal et al evaluated putative prognostic factors in metastatic STS and showed that low serum albumin (<4 g/dl) is significantly associated with a poor event‐free survival (EFS) in uni‐ and multivariate analysis. Their patient collective included 110 patients with different types of STS . In line with these findings, the present study showed a significantly lower recurrence‐free survival in sarcoma patients with low serum albumin values.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Iqubal et al evaluated putative prognostic factors in metastatic STS and showed that low serum albumin (<4 g/dl) is significantly associated with a poor event‐free survival (EFS) in uni‐ and multivariate analysis. Their patient collective included 110 patients with different types of STS . In line with these findings, the present study showed a significantly lower recurrence‐free survival in sarcoma patients with low serum albumin values.…”
Section: Discussionsupporting
confidence: 86%
“…Their patient collective included 110 patients with different types of STS. 49 In line with these findings, the present study showed a significantly lower recurrence-free survival in sarcoma patients with low serum albumin values. Panotopoulos and co-workers analyzed 84 patients affected by liposarcoma and proved poorer overall and disease-specific survival in patients with presurgical values of albumin under 35 g/L.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This was also found recently in an Indian study which showed that patients with extremity tumours and patients with multimodality treatment had a favourable prognosis, suggesting that the possibility of aggressive treatment of the primary tumour localization may result in a better survival. (26) Tumour site is also a known prognostic factor in surgically treated non-metastatic sarcoma patients. (27) Time since initial diagnosis behaves differently as prognostic factor between patients with LAD (both a very short time and a very long time from initial diagnosis were associated with a favourable prognosis) and both the other groups (only a long time interval from initial diagnosis having a favourable diagnosis).…”
Section: Discussionmentioning
confidence: 99%